The practices of contract farming among fresh fruit and vegetable suppliers in Malaysia - Man, Norsida (Science Publications, 2010)
Problem statement: Contract Farming (CF) concept is an agreement between buyers and producers, where by producers agree to produce and supply agriculture products according to the agreed quantity, quality, variety, grade, type of packaging and time of delivery. The two parties will mutually agree on the pricing of product, either on a contract price or a market price. Therefore, CF is seen as a tool for fostering smallholder participation in new high-value product markets and improving quality standards, thus increasing and stabilizing smallholder incomes. In Malaysia, CF has been identified as a system capable of stimulating agricultural production and was given a central role in the latest strategy by government to improve the vegetable and fruit production. Approach: The overall objective of this study was to examine CF as the new marketing practice among selected vegetable and fruit suppliers. The specific objectives of the study were: (1) to examine the respondents' perception towards CF; (2) to identify respondents' practices toward the CF and (3) to suggest a policy to ensure the sustainability of CF. Results: Out of 208 of the total respondents selected in the study, 41 suppliers were involved in CF. The data were analyzed using SPSS to describe the respondents’ profile and current supply chain practices. At present, the suppliers have a contract agreement with Federal Agriculture Marketing Authority (FAMA) and FAMA has a contract agreement with Hypermarkets. It is presumed that there is a new supply chain network but the contract was not according to the FAO definition. The production and marketing contracts exist in non-formal or mainly verbal agreement. The production contract respondents also did not follow the criteria of CF. Conclusion: Because of this, all the non-formal production contracts in this survey are categorized into marketing contracts. This study concludes with the absence of proper farming contract between farmers and hypermarkets.